Rational Design of Superoxide Dismutase (SOD) Mimics: The Evaluation of the Therapeutic Potential of New Cationic Mn Porphyrins with Linear and Cyclic Substituents - Tovmasyan, Artak; Carballal, Sebastian; Ghazaryan, Robert; Melikyan, Lida; Weitner, Tin; Maia, Clarissa G. C; Reboucas, Julio S; Radi, Rafael; Spasojevic, Ivan; Benov, Ludmil; Batinic-Haberle, Ines (Inorganic chemistry, 2014)
Our goal herein has been to gain further insight into the parameters which control porphyrin therapeutic potential. Mn porphyrins (MnTnOct-2-PyP5+, MnTnHexOE-2-PyP5+, MnTE-2-PyPhP5+, and MnTPhE-2-PyP5+) that bear the same positive charge and same number of carbon atoms at meso positions of porphyrin core were explored. The carbon atoms of their meso substituents are organized to form either linear or cyclic structures of vastly different redox properties, bulkiness, and lipophilicities. These Mn porphyrins were compared to frequently studied compounds, MnTE-2-PyP5+, MnTE-3-PyP5+, and MnTBAP3–. All Mn(III) porphyrins (MnPs) have metal-centered reduction potential, E 1/2 for MnIIIP/MnIIP redox couple, ranging from −194 to +340 mV versus NHE, log k cat(O2 •–) from 3.16 to 7.92, and log k red(ONOO–) from 5.02 to 7.53. The lipophilicity, expressed as partition between n-octanol and water, log P OW, was in the range −1.67 to −7.67. The therapeutic potential of MnPs was assessed via: (i) in vitro ability to prevent spontaneous lipid peroxidation in rat brain homogenate as assessed by malondialdehyde levels; (ii) in vivo O2 •– specific assay to measure the efficacy in protecting the aerobic growth of SOD-deficient Saccharomyces cerevisiae; and (iii) aqueous solution chemistry to measure the reactivity toward major in vivo endogenous antioxidant, ascorbate. Under the conditions of lipid peroxidation assay, the transport across the cellular membranes, and in turn shape and size of molecule, played no significant role. Those MnPs of E 1/2 ∼ +300 mV were the most efficacious, significantly inhibiting lipid peroxidation in 0.5–10 μM range. At up to 200 μM, MnTBAP3– (E 1/2 = −194 mV vs NHE) failed to inhibit lipid peroxidation, while MnTE-2-PyPhP5+ with 129 mV more positive E 1/2 (−65 mV vs NHE) was fully efficacious at 50 μM. The E 1/2 of MnIIIP/MnIIP redox couple is proportional to the log k cat(O2 •–), i.e., the SOD-like activity of MnPs. It is further proportional to k red(ONOO–) and the ability of MnPs to prevent lipid peroxidation. In turn, the inhibition of lipid peroxidation by MnPs is also proportional to their SOD-like activity. In an in vivo S. cerevisiae assay, however, while E 1/2 predominates, lipophilicity significantly affects the efficacy of MnPs. MnPs of similar log P OW and E 1/2, that have linear alkyl or alkoxyalkyl pyridyl substituents, distribute more easily within a cell and in turn provide higher protection to S. cerevisiae in comparison to MnP with bulky cyclic substituents. The bell-shape curve, with MnTE-2-PyP5+ exhibiting the highest ability to catalyze ascorbate oxidation, has been established and discussed. Our data support the notion that the SOD-like activity of MnPs parallels their therapeutic potential, though species other than O2 •–, such as peroxynitrite, H2O2, lipid reactive species, and cellular reductants, may be involved in their mode(s) of action(s).